Fibrinogen-to-Albumin Ratio as a Novel Predictor of Intracerebral Hemorrhage in Maintenance Hemodialysis Patients - He X; Wang Y; Wang Y; Li X (Journal of Inflammation Research, 2025)
Xiaojie He,1,* Yaqing Wang,2,* Yuqing Wang,1,* Xiaodong Li3 1Graduate School of Hebei Medical University, Shijiazhuang, Hebei, 050017, People’s Republic of China; 2Graduate School of Chengde Medical University, Chengde, Hebei, 06700, People’s Republic of China; 3Department of Nephrology, Baoding No. 1 Central Hospital of Hebei Medical University, Baoding, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaodong Li, Department of Nephrology, Baoding No.1 Central Hospital of Hebei Medical University, Baoding Great Wall North Street No 320, Baoding, Hebei, 071000, People’s Republic of China, Email lxd_765@sina.comObjective: Intracerebral hemorrhage (ICH) is a life-threatening complication in patients undergoing maintenance hemodialysis (MHD), yet reliable biomarkers for early risk stratification remain scarce. The fibrinogen-to-albumin ratio (FAR), a composite inflammatory and nutritional marker, may offer predictive value for ICH in this high-risk population.Methods: This retrospective study analyzed a total of 536 MHD patients (ICH group: n=207; non-ICH group: n=329) from June 2019 to June 2024. FAR was calculated based on laboratory parameters. Multivariate Logistic regression analysis was used to identify independent risk factors for ICH, and ROC curve analysis and restricted cubic spline (RCS) modeling were used to assess the predictive performance of FAR for cerebral hemorrhage in maintenance hemodialysis patients. Finally, the DeLong test was used to compare the differences in area under curve (AUC).Results: Logistic regression analysis revealed that FAR ([OR] 1.07, 95% [CI] 1.03– 1.10, p< 0.001) was the independent predictor of ICH. Trend testing showed a dose-response correlation between FAR (p for trend < 0.001) and ICH risk. RCS showed a non-linear correlation between FAR and ICH risk (non-linear p=0.029). ROC analysis demonstrated FAR’s superior accuracy (AUC=0.75) compared to fibrinogen (AUC=0.67) and albumin (AUC=0.49), identifying 12.2 as the optimal cutoff (sensitivity=0.73, specificity=0.60). The DeLong’s test confirm that FAR exhibits significantly superior discriminatory performance.Conclusion: FAR may predict the occurrence of ICH in MHD patients. This study explores the application value of FAR in predicting ICH risk in MHD patients, providing a new biomarker for early identification of high-risk patients in clinical practice.Keywords: fibrinogen to albumin ratio, intracerebral hemorrhage, fibrinogen, albumin, maintenance hemodialysis